Supervised internship in health psychology during the pandemic of COVID-19 at the Hospital Santa Casa de Misericórdia do Pará (Research, Society and Development, 2021)
Health psychology professionals can act in low complexity and high complexity directed to HC's (General Hospitals), according to their specificity. In this sense, the health psychology professional should provide empathic listening, aiming to minimize the helpless hood experienced by the patient and also work on the thoughts and emotions influenced by non-pleasant experiences, given the possibility to resinify their experiences, establishing autonomy and responsibility in relation to health care. This study is qualitative in nature that aimed to report the experiences of the students of the Bachelor of Psychology course through the experiences of the supervised internship in health psychology in the hospital field, during the COVID-19 pandemic. A descriptive and observational method of the aspects experienced by psychology students during the mandatory internship at the Santa Casa de Misericórdia hospital in Belém was used, specialized in the ambulatory treatments of premature infants, women, pediatrics, surgical and clinical specialties, using instruments such as: conversation wheel about the performance of professionals, observation of the environment, description of organizational experience and intervention of the psychologist's work. Please note, the importance of the internship in health for the favoring of personal growth, in the rescue of autonomy, in the exercise of leadership and in decision-making, important tools in professional life that will support the exercise of the profession. In addition, it is evident the effectiveness of psychological science in health actions and how much the internship in the hospital enables several important experiences, due to the that, when entering hospital psychology, there is a world within the hospital, lives, cultures, histories, totally differentiated ideologies and with unique particular cases that give the professional a daily challenge of intervention and to keep up to date in literature.